2012
DOI: 10.1111/j.1365-2923.2012.04332.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological analysis of patient experiences of medical student teaching encounters

Abstract: Provided they receive the clinical care for which they are attending a consultation and are treated respectfully, patients may sometimes willingly become 'objects' from which students learn. They may, however, become more deeply engaged in teaching consultations in which they participate actively in a triadic relationship of mutual benefit with a doctor and student. Teaching consultations call for doctors to be sensitive and adaptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 37 publications
1
39
0
1
Order By: Relevance
“…Interpretative and reflexive thoughts and ideas were recorded in memos. A subset of four transcripts was then analyzed, during which themes were revised, split and clustered under broader themes, resulting in an initial template [21,24]. This template was developed into a network depicting the relationships between themes and how low hierarchy themes could be associated with multiple high hierarchy themes.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretative and reflexive thoughts and ideas were recorded in memos. A subset of four transcripts was then analyzed, during which themes were revised, split and clustered under broader themes, resulting in an initial template [21,24]. This template was developed into a network depicting the relationships between themes and how low hierarchy themes could be associated with multiple high hierarchy themes.…”
Section: Discussionmentioning
confidence: 99%
“…Isto porque, muitas vezes, pressupõe-se a Pode-se perceber que o entrevistado adjetiva a visita mé-dica com os termos bonito/bom por entender seu objetivo ligado à formação médica e à transmissão de conhecimentos. Dados semelhantes foram encontrados numa pesquisa em que os entrevistados avaliaram ser importante o médico ajudar os estudantes inseguros da prática médica, auxiliando a torná-los mais confiantes, beneficiando os alunos e, consequentemente, a sociedade 20 . Em ambas as pesquisas, os pacientes veem como algo belo a "reunião" e a "união" dos médicos no momento da visita em prol do aprendizado.…”
Section: Oxente E é Essa Boiada Todinha é Eu Não Tô Entendendo Nãounclassified
“…Studies have also revealed that patients may express concerns about students’ access to patient records and discussing personal matters. Patients’ negative statements are also related to encountering uncertain or disinterested students and exclusion of communication between student and supervisor [5-8]. …”
Section: Introductionmentioning
confidence: 99%